The Effectiveness of Internal Audit in Achieving Good Governance - Dimas Bagus Williyanto; Moeljadi; Soedjatno (Universitas Muhammadiyah Malang, 2025)
Purpose: This study examines the role of internal audits in promoting good governance in the public sector. Methodology/approach: A qualitative approach with a case study method was employed. Data were collected through document analysis, interviews with ten auditors and two auditees, and a focus group discussion (FGD) with Parepare Local Government Internal Audit teams. The data were analyzed using thematic analysis. Findings: The study found that internal audits significantly contribute to good governance. However, challenges such as limited technical proficiency, high staff turnover, and inadequate follow-up on audit recommendations reduce their effectiveness. Additionally, lack of direct communication and incomplete distribution of audit reports to auditees hinder implementation. Practical implications: The findings emphasize the need to improve auditor competence, management support, and follow-up processes to enhance the effectiveness of internal audits in public sector governance. Originality/value: This study contributes to understanding how internal audit impacts good governance based on four dimensions: input, process, output, and outcome. It also offers valuable insights into public sector audit practices, particularly in developing countries.